Oral Cavity Manifestation in Menopausal Women - Azarsa, Amir; Mahmoodii, Lina; Gakharia, Tatia (Caucasus Journal of Health Sciences and Public Health, 2020)
Large numbers of symptoms, from physical to mental, are associated with menopause. For the same purposes as with other body systems, menopause affects a woman’s oral and dental health .Severity of oral manifestations occurring in postmenopausal women.These symptoms may have a negative effect on oral health and the treatment needs that dentists should be aware of perimenopausal, menopausal, post menopausal women’s symptoms and health care needs. This review article has emphasized on the diverse oral presentations of postmenopausal women by literature review of various relevant articles and recent studies selected references and internet services using the PubMed, Science Direct, EBSCO data bases about oral health in menopausal and concepts of underlying mechanisms associated with these post menopausal conditions. In reviewing these concepts ,In this article we will focus on oral health complications that are caused by menopause and review the actual aspects of associated prosthodontic effects in postmenopausal period women and current recommendationsin the field of menopause and oral health.